EXAMEN ESPECIAL AL COMPONENTE INVERSIONES EN BIENES DE LARGA DURACIÓN DEL GOBIERNO AUTÓNOMO DESCENTRALIZADO DEL CANTÓN ATAHUALPA DE LA PROVINCIA DE EL ORO, PERÍODO 2014 - Salinas Jumbo, Ana Cristina (2016)
The development of this thesis main objective was to develop a Special Examination Component Capital Expenditures Long Term Decentralized Autonomous Government of Atahualpa Canton of the Province of El Oro for the period 2014 to apply the various stages of the process to obtain information, analyze and identify existing shortcomings regarding the administration of goods in the institution. Thus the process of internal control relevant to the investment in durable goods in the Autonomous Government Decentralized Canton Atahualpa by using programs examination and internal control questionnaires which in turn allowed to determine various findings which are also evaluated were reflected narratives bonds with their respective comments, conclusion and recommendation. In the same way it was proposed to examine the documentation supporting the transactions relating to investment in durable goods, by reviewing the procurement process conducted in the state, to check for documents that support acquisitions and whether they comply with the legality and accuracy requirements. Another objective was to verify that the information and procedures are complied with the laws and regulations governing the management and investment of assets. Furthermore it was proposed to develop a report 5 containing the facts found and that it will help for proper decision-making by the highest authority of the entity. The methodology used to develop the thesis was in the first instance to issue the work order and initial notification to communicate the start of work, then it continued with the implementation of the three phases of the special examination: First, Planning; beginning with the previous visit to the institution in which the same information was gathered to proceed to elaborate preliminary planning and specific planning with the latter being able to determine the risk involved in internal control, identified in the Matrix risks; then he proceeded to the second phase: the Execution of Test, where Programs Examination was made by applying a series of procedures that made possible the preparation of working papers on which records the most important findings mentioned in narratives bonds Additional evidence of purchases was collected, adjustments and reclassifications were made to finally Communicate with the Results presentation of the final report of the review made by their respective comments, conclusions and recommendations. And finally it is concluded that the institution applying the rules governing the conservation and wise use of goods is lacking on the part of those responsible, so that they are at risk of loss or obsolescence not fulfill his life